Nurturing Hope Through Reciprocity: High Park’s Black Oak Savannah - Bachner, Ingrid (YU-WRITE: Journal of Graduate Student Research in Education, 2023)
Climate change has become a mainstream concern, with proposed solutions focusing on mitigating the impact of environmental degradation on human lives. I use Toronto’s High Park as a case study to explore why an essential aspect of achieving profound and enduring environmental restoration involves recognizing the deep interconnectedness between human beings and what we commonly refer to as “nature”. High Park’s black oak savannah was managed for thousands of years by Indigenous peoples, who used fire to maintain the savannah’s open canopy and activate seeds. European colonization halted these burns, leading to most of the savannah being lost to closed-canopy forests and invasive plants; globally, less than one percent of oak savannah ecosystems remain. Amid despair, we rekindle our hope through prescribed burns, stewardship programs, and the planting of grasses and wildflowers with long-stand relationships with the land; we know that hope is a discipline where collective commitment and action are essential. Indigenous knowledge and storytelling remind us of our responsibility of reciprocity to the land and all our relations. We sow these seeds of hope and trust they will flourish and generate new life, much like ancestral seeds activated by fire.